Associations of Adiponectin and Leptin with Incident Coronary Heart Disease and Ischemic Stroke in African Americans: The Jackson Heart Study - Bidulescu, Aurelian; Liu, Jiankang; Chen, Zhimin; Hickson, DeMarc A.; Musani, Solomon K.; Samdarshi, Tandaw E.; Fox, Ervin R.; Taylor, Herman A.; Gibbons, Gary H. (Frontiers in Public Health, 2013)
Background: Because the predictive significance of previously reported racial differences in leptin and adiponectin levels remains unclear, we assessed the prospective association of these adipokines with the risk of cardiovascular disease (CVD) events in African Americans, a population with a high prevalence of cardiometabolic risk factors. Methods: Serum specimens from 4,571 Jackson Heart Study participants without prevalent CVD at baseline examination (2000-2004) were analyzed for adiponectin and leptin levels. Cox proportional hazard regression models were used to estimate the associations of the two adipokines with incident coronary heart disease and incident ischemic stroke. Results: During 6.2 years average of follow-up, 98 incident coronary heart disease and 87 incident ischemic stroke events were documented. Among study participants (64% women; mean age 54 ± 13 years), the mean (standard deviation, SD) was 6.04 (4.32) µg/mL in women and 4.03 (3.14) µg/mL in men for adiponectin and 37.35 (23.90) ng/mL in women and 11.03 (10.05) ng/mL in men for leptin. After multivariable adjustment that included age, body mass index, high-density lipoprotein cholesterol, triglycerides, insulin resistance by HOMA-IR, systolic blood pressure, hypertension medication, smoking and physical activity, adiponectin was directly associated in women with incident stroke, HR = 1.41 (1.04 - 1.91) per 1 SD increase (p = 0.03), but not in men (p = 0.42). It was not associated with incident coronary heart disease in women or men. Leptin was not associated with incident coronary heart disease or incident stroke. Conclusions: In the largest community-based African American cohort, adiponectin was associated among women with a higher risk of incident stroke. Whether adiponectin harbors harmful properties, or it is produced in response to vascular inflammation to counter the atherosclerotic process, or the putative 'adiponectin resistance' phenomenon acts, should be further assessed.